Soil Properties Variability Under Various Agroecosystems In Ultisols Of Bengkulu - Priyono Prawito; Impetus Hasada Windu Sitorus; Zainal Muktamar; Bandi Hermawan; Welly Herman (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2021)
Understanding the relation of agroecosystem types, ages, and soil properties are vital in maintaining good quality soil. This study aims to explore the variation of selected soil properties with agroecosystem types and ages. The research has been conducted in North Bengkulu, Indonesia. Soil properties on agroecosystems of 5-yr, 10-yr, 15-yr oil palm plantation, 5-yr, 10-yr, 15-yr rubber plantation, food cropland, and scrubland were evaluated. The study found that soil in oil palm and rubber plantations of any age have a similar texture, bulk density (BD), and actual soil moisture (ASM). All plantation agroecosystems and scrubland have higher clay and lower silt content than that in food cropland. In addition, the scrubland has the highest ASM content among the agroecosystems. On the other hand, both agroecosystems enhances soil chemical properties than food cropland and scrubland as indicated by the improvement of organic-C, total-N, available P, exchangeable K and CEC of Ultisols. Older plantation also provides higher soil chemical improvement than younger one. This finding is significant for management of sub optimal soil mainly Ultisols for oil palm and rubber plantation.